Encyclopedia of demons in world religions and cultures - Bane, Theresa (McFarland, 2012)
"This volume catalogs nearly three thousand demons in the mythologies and lore of virtually every ancient society and most religions. Entries offer descriptions, demon's origins, appearance, and cultural significance. Also included are descriptions of the demonic and diabolical members making up the hierarchy of Hell and the numerous species of demons that populate the earth and plague mankind"--Provided by publisher